Pengaruh kepemilikan institusional, kepemilikan publik dan profitabilitas terhadap penghindaran pajak dengan manajemen laba sebagai variabel intervening - Kusumadewi, Yunita; Edastami, Mayangsari (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The purpose of this study was to determine whether there is an effect of institutional ownership, public ownership and profitability variables on tax avoidance with earnings management as the intervening variable..The research approach used in this research is quantitative research with causality type. The sample used was 13 companies during the 6-year study period (2015-2020) or 78 samples. Hypothesis testing using Sobel test (criteria from mediation). Sobel test is used to determine the effect of the mediating variable, namely earnings management. Based on the results of the tests that have been carried out, this study concludes that institutional ownership and public ownership have no effect on earnings management. profitability have an effect on earnings management.However, institutional ownership and profitability have no effect on tax avoidance, public ownership have an effect on tax avoidance. Meanwhile, earnings management is not able to mediate the variables of institutional ownership, public ownership and profitability on tax avoidance.